Medicinal plants popularly used for gastrointestinal disorders in Costa Rican Central Valley - Tamayo Castillo, Giselle (2004)
Abstract : A survey was conducted of medicinal plants for gastrointestinal disorders used by inhabitants of the Central Valley in Costa Rica by means of interviews with medicinal plant vendors of the central markets of the cities of Alajuela, Cartago, Heredia and San Jose. Fifteen medicinal plants and one plant mixture were recorded; the last one was prepared in situ by the vendor upon request and its components varied according to the availability of plants. A qualitative chromatographic comparison was made on the patterns of plants from different origin and different times of the year. Differences were noticed with regard to the concentration of major components in many plants. A quantitative method using HPLC was used to examine Quassia amara and Plantago major.